2020
DOI: 10.1177/0193945920921101
|View full text |Cite
|
Sign up to set email alerts
|

Social Support, Self-Efficacy, and Psychological Wellbeing of Adults with Type 2 Diabetes

Abstract: Social support improves self-efficacy, which in turns enhances self-management that lead to better psychological outcomes of persons with type 2 diabetes (T2D). The purpose of this study was to examine the relationship between social support and psychological outcomes of adults with T2D. A cross-sectional design was used to recruit a sample of 339 participants from a diabetes clinic. The participants responded to a series of questionnaires on demographics, social support dimensions, and self-management; self-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 44 publications
7
41
1
1
Order By: Relevance
“…We observed a trend where high social support was associated with better self‐management among women; the level of social support did not appear to be associated with self‐management among men. This is consistent with previous literature, whereby benefits derived from social support varied by gender, likely as a result of cultural and situational context (Al‐Dwaikat et al, 2020 ). For example, a qualitative study revealed that women tended to report greater influence from a wider group of people in their social support networks, since they were more likely than men to disclose their diabetes to others (Mathew et al, 2012 ).…”
Section: Discussionsupporting
confidence: 92%
“…We observed a trend where high social support was associated with better self‐management among women; the level of social support did not appear to be associated with self‐management among men. This is consistent with previous literature, whereby benefits derived from social support varied by gender, likely as a result of cultural and situational context (Al‐Dwaikat et al, 2020 ). For example, a qualitative study revealed that women tended to report greater influence from a wider group of people in their social support networks, since they were more likely than men to disclose their diabetes to others (Mathew et al, 2012 ).…”
Section: Discussionsupporting
confidence: 92%
“…It is generally believed that social support is an important aspect of psychological adjustment in previous study [ 55 ]. Moreover, previous study’s have shown that social support had an indirect correlation with the psychological health of diabetic patients [ 56 ]. Also, in Kaholokula study, DR patients with a lower social support and a worse physical health are likely to experience a high probability of depression [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy is an important mediator between social support and health. Integrated interventions of promoting perceived social support may be effective in enhancing self-efficacy [ 46 ]. Elderly people face life adversities, poor social support, and limited access to health services, which may affect their health self-efficacy [ 47 ].…”
Section: Discussionmentioning
confidence: 99%